Dupilumab significantly improves skin barrier function in patients with moderate‐to‐severe atopic dermatitis. Issue 11 (21st July 2022) - Berdyshev, Evgeny; Goleva, Elena; Bissonnette, Robert; Bronova, Irina; Bronoff, Anna Sofia; Richers, Brittany N.; Garcia, Shannon; Ramirez‐Gama, Marco; Taylor, Patricia; Praestgaard, Amy; Agueusop, Inoncent; Jurvilliers, Pauline; et al.
Abstract: Background: Atopic dermatitis (AD) is characterized by abnormal skin lipids that are largely driven by hyperactivated type 2 immune responses. The antibody to the α‐subunit of interleukin (IL)‐4 receptor, dupilumab, was recently approved to treat AD and demonstrated strong efficacy. However, the role of dupilumab therapy in the regulation of skin barrier structure and function has not been fully explored. Methods: We have evaluated the content of lipids and transepidermal water loss (TEWL) in lesional and non‐lesional skin of adults and adolescents with moderate‐to‐severe AD over the course of 16‐week treatment with dupilumab and compared those values with that of matched healthy volunteers. Results: Dupilumab treatment provided a significant decrease in TEWL in AD lesions, lowering it almost to the levels seen in the skin of healthy subjects. Blocking IL‐4/IL‐13 signaling with dupilumab normalized lipid composition (decreased levels of ceramides with non‐hydroxy fatty acids and C18‐sphingosine and increased the level of esterified omega‐hydroxy fatty acid‐containing ceramides) and increased ceramide chain length in lesional as well as non‐lesional stratum corneum of AD patients. Partial changes for these parameters were already observed after 2 weeks, with a full response achieved after 8 weeks of dupilumab treatment. Conclusions: Inhibition of IL‐4/IL‐13 signaling by dupilumab allows restoration of skin lipid composition and barrier function in patients with moderate‐to‐severe AD. Abstract : Skin barrier function is in part determined by stratum corneum lipids. Their composition is impaired in AD skin due to excessive signaling. by IL‐4 and IL‐13. Blocking IL‐4/IL‐13 signaling by a biologic dupilumab restores stratum corneum lipid composition and skin barrier function in AD patients.Abbreviations: AD, atopic dermatitis; EOS‐ceramides, ceramides containing esterified omega hydroxy fatty acids and sphingosine; IL, interleukin; NS‐ceramides, ceramides with non‐hydroxy fatty acids and sphingosine; TEWL, transepidermal water loss